REVITALIZATION OF REGIONAL-OWNED ENTERPRISE (BUMD) GOVERNANCE THROUGH THE PARTICIPATION IN OIL AND GAS MANAGEMENT BY USING GROSS SPLIT MECHANISM - Yudho Taruno Muryanto; Tuhana Tuhana; Anjar Sri Ciptorukmi (Faculty of Law, Universitas Sebelas Maret, 2020)
The implementation of the gross split scheme in the upstream oil and gas business by revenue sharing contract is a new phase concerning the existence, especially for regional governments related to the insertion of regional assets. The participation of BUMD in the oil and gas management where the BUMD is located is prominent, in the context of increasing revenue and boosting the regional economy. The involvement of BUMD in oil and gas management is mainly related to the gross split mechanism. There are several problems, among others, related to the problematic management of BUMD whose business activities support the upstream oil and gas business to increase local revenue and how to implement the revitalization of BUMD governance that supports the upstream oil and gas business. This article is the result of empirical legal research by using a conceptual approach. Research techniques and data collection using primary and secondary material by analyzing the data through text interpretation (hermeneutics) and the logic of deduction. Based on the research on the revitalization of BUMD governance in the upstream oil and gas business that uses a gross split mechanism, there are several problems in its management, including overlapping sectoral arrangements regarding BUMD between one regulation with other regulations, management issues, human resources issue, supervision and guidance of BUMD, and restructuring of BUMD.